Determinants of managers' behaviour in a crisis situation in an enterprise - an attempt at model construction = Uwarunkowania zachowań kadry kierowniczej w sytuacji kryzysu w przedsiębiorstwie - próba budowy modelu - Walecka, Anna (Zielona Góra: Faculty of Economics and Management Press)
A crisis in an enterprise is an extremely diffi cult situation which company managers need to deal with. The enterprise may take all kinds of remedial actions. Ranging from conservative measures, through moderate to very radical ones. These steps may be aimed at counteracting the effects of the past or focused on looking towards the future of the organisation.
Keywords: przedsiębiorstwo; kryzys w przedsiębiorstwie; zachowania menedżerów; determinanty zachowań; enterprises; crisis in the enterprise; managers behaviour; determinants of behaviour